MANUAL TÉCNICO: MANEJO INTEGRADO DEL CULTIVO DE PAPA - Arcos Pineda, Jesús; Mamani Huayta, Hector; Barreda Quispe, Wilfredo Lino; Holguín Chuquimamani, Vitaliano (Instituto Nacional de Innovación Agraria, 2020)
35 Páginas